EFEKTIVITAS TERAPI HIPNOTIS LIMA JARI TERHADAP KECEMASAN IBU PRE PARTUM DI KLINIK CHELSEA HUSADA TANJUNG BERINGIN KABUPATEN SERDANG BEDAGAI - Marbun, Agnes; Pardede, Jek Amidos; Perkasa, Surya Indah (Universitas Prima Indonesia, 2019)
Labor in pregnant women will result in various psychological problems for pregnant women, one of which is anxiety. Anxiety in pregnant women if not handled seriously will have an impact on the physical and psychological effects, both on the mother and on the fetus. One non-pharmacological therapy that can reduce anxiety is five-finger hypnosis, where this therapy can reduce muscle tension, help focus attention and reduce fear. The purpose of this study was to determine the effectiveness of five-finger hypnosis therapy on pre-partum maternal anxiety. This study uses the one group pre and post test quasy experiment method which aims to determine the effectiveness of before and after five finger hypnosis therapy on pre-partum maternal anxiety. The population was in this study were all pre-partum mothers of 180 people. The sampling technique uses a quota sampling of 15 people. The measuring instrument uses an anxiety questionnaire, the Hamilton Anxiety Rating Scale. Analysis is using the Wilcoxon test with p value <0.005. The results showed that the effectiveness of five-finger hypnosis therapy on pre-partum maternal anxiety resulted in p value = 0.001. It is recommended to the clinic to be able to provide information about the action of five-finger hypnosis therapy and can train pregnant women who will give birth so that the mother can know the benefits and the right way to eliminate anxiety at the time of delivery.